2021
DOI: 10.1007/s11695-021-05724-z
|View full text |Cite
|
Sign up to set email alerts
|

Religious Fasting of Muslim Patients After Metabolic and Bariatric Surgery: a Modified Delphi Consensus

Abstract: Background Fasting during Ramadan is one of the five pillars of the Muslim faith. Despite the positive effects of fasting on health, there are no guidelines or clear recommendations regarding fasting after metabolic/bariatric surgery (MBS). The current study reports the result of a modified Delphi consensus among expert metabolic/bariatric surgeons with experience in managing patients who fast after MBS. Methods A committee of 61 well-known metabolic and bariatric surgeons from 24 countries was created to part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“… 15 , 17 Other studies showed that poor quality of sleep may increase glycated hemoglobin level. 18 In addition, in non-diabetic people, drastic changes occur in terms of energy and water intake and glucose homeostasis. The time between meals is longer than outside Ramadan, meals are more consistent and are taken exclusively during the night.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 17 Other studies showed that poor quality of sleep may increase glycated hemoglobin level. 18 In addition, in non-diabetic people, drastic changes occur in terms of energy and water intake and glucose homeostasis. The time between meals is longer than outside Ramadan, meals are more consistent and are taken exclusively during the night.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of RF on the risk of diabetic emergencies was the subject of two different original studies of different designs and contrasting findings. 24,25 First, AlZahrani et al 26 examined the variation in visits at the emergency room (ER) during Ramadan compared with other lunar months at a tertiary care hospital in Jeddah city concerning diabetes emergencies. A retrospective study was conducted by electronic medical record review of patients aged 18 years and older with diabetes emergencies who visited the ER of a military hospital from the 9th to 11th lunar months during 2017 to 2018 for diabetes-related emergencies.…”
Section: Diabetic Emergenciesmentioning
confidence: 99%
“…A committee of 61 well-known MBS from 24 countries was created to participate in the Delphi consensus (Kermansaravi et al). 25 The decision regarding fasting must be coordinated among the surgeon, the nutritionist, and the patient. At any time after MBS, 96.7% advised stopping fasting in the presence of persistent symptoms of intolerance.…”
Section: Highlights Of the Literaturementioning
confidence: 99%
“…The literature search on fasting and bariatric surgery produced a total of 4 articles. Included was 1 prospective study [2], a subsequent commentary on that specific published article challenging the methodology and results [5], and a recently published modified Delphi Consensus on religious fasting of Muslim patients after MBS [6]. In addition, there was mention of recommendations for fasting in 1 nutritional clinical practical guideline (CPG) for bariatric surgery by Dagan et al [7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To date, there is a single prospective study regarding fasting after MBS and a commentary that followed [2,5]. More recently, a modified Delphi Consensus on Ramadan religious fasting after MBS was published [6]. In a prospective study by Al-Ozairi et al [2], the researchers investigated calorie and nutrient consumption, appetite, satiety, and lifestyle behaviors in male and female patients from Kuwait who had the sleeve gastrectomy (SG) and were fasting for Ramadan.…”
Section: Fasting and Bariatric Surgerymentioning
confidence: 99%